Reviewing The Firm Value In Terms Of Profit, Debt, And Growth - Nur Wahyuni; Achriansyah Achmad Gani (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to examine the effect of Return on Equity (ROE), Return on Assets (ROA), Non-Profit Margin (NPM), DER (Debt to Asset Ratio), Debt to Asset Ratio (DAR), Asset Growth, and Market To Book Value of Equity (MBVE) to Price Book Value (PBV). The population in this study is the consumer goods sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the observation period from 2019 to 2021. There are 42 companies. The total sample in this study is 33 financial statement data, which was determined based on the purposive sampling method. The data were analyzed using the Ordinary Least Square model using the Eviews Version 12 software. The results found that ROE, ROA, Asset Growth, and Market To Book Value of Equity (MBVE) positively and significantly affected firm value. Meanwhile, DER (Debt to Equity Ratio) has a negative and significant effect on firm value. Meanwhile, DAR has no significant adverse effect on firm value.